Periprocedural Changes of NT‐proBNP Are Associated With Survival After Transcatheter Aortic Valve Implantation. Issue 3 (5th February 2019) - Seoudy, Hatim; Frank, Johanne; Neu, Markus; Güßefeld, Nathalie; Klaus, Yannic; Freitag‐Wolf, Sandra; Lambers, Moritz; Lutter, Georg; Dempfle, Astrid; Rangrez, Ashraf Yusuf; Kuhn, Christian; Frey, Norbert; et al.
Abstract : Background: Cardiovascular biomarkers constitute promising tools for improved risk stratification and prediction of outcome in patients undergoing transcatheter aortic valve implantation. We examined the association of periprocedural changes of NT‐proBNP (N‐terminal pro–B‐type natriuretic peptide) with survival after transcatheter aortic valve implantation. Methods and Results: NT‐proBNP levels were measured in 704 patients before transcatheter aortic valve implantation and at discharge. Patients were grouped as responders and nonresponders depending on an NT‐proBNP–based ratio (postprocedural NT‐proBNP at discharge/preprocedural NT‐proBNP). Overall, 376 of 704 patients showed a postprocedural decrease in NT‐proBNP levels (NT‐proBNP ratio <1). Responders and nonresponders differed significantly regarding median preprocedural (2822 versus 1187 pg/mL, P <0.001) and postprocedural (1258 versus 3009 pg/mL, P <0.001) NT‐proBNP levels. Patients in the nonresponder group showed higher prevalence of atrial fibrillation (47.0% versus 39.4%, P =0.042), arterial hypertension (94.2% versus 87.5%, P =0.002), renal impairment (77.4% versus 69.1%, P =0.013), and peripheral artery disease (24.4% versus 14.6%, P =0.001). In contrast, patients in the responder group had higher prevalence of moderately reduced left ventricular ejection fraction (17.3% versus 11.0%, P =0.017), lower calculated aortic valve area (0.7 versus 0.8 cm 2, P <0.001), and higher mean pressure gradient (41 versus 35 mm Hg, P <0.001). Median follow‐up was 22.6 months. Kaplan–Meier analysis showed a highly significant survival benefit for the responder group compared with the nonresponder group (log‐rank test, P <0.001). Conclusions: A ratio based on periprocedural changes of NT‐proBNP is a simple tool for better risk stratification and is associated with survival in patients after transcatheter aortic valve implantation.